Boston Type 1 Keratoprosthesis for Gelatinous Drop-Like Corneal Dystrophy. Issue 6 (June 2016) - Lekhanont, Kaevalin; Jongkhajornpong, Passara; Chuephanich, Pichaya; Inatomi, Tsutomu; Kinoshita, Shigeru
ABSTRACT: Purpose: To report the outcomes of Boston type 1 keratoprosthesis in the management of advanced gelatinous drop-like corneal dystrophy (GDLD). Methods: A retrospective, noncomparative, interventional case series was conducted at Ramathibodi Hospital, Bangkok, Thailand. Four eyes of three siblings with molecularly and histologically confirmed GDLD from a Thai family underwent an uneventful Boston type 1 keratoprosthesis implantation for visual rehabilitation. Clinical data were obtained from a review of the medical records. Visual acuity, device retention, and postoperative complications were the main outcome measures. The follow-up ranged from 8 to 96 months. Results: One eye received keratoprosthesis surgery as a primary penetrating procedure. The other three eyes had the surgery as a secondary procedure after graft failure. Best-corrected visual acuity was favorably improved from counting fingers to 20/25 in two eyes, from hand movement to 20/20 in one eye, and from hand movement to counting fingers at 2 feet in one eye caused by severe amblyopia. The improved vision was maintained for 8 months to 6.2 years after surgery. Postoperative complications included disease recurrence in the donor graft (N = 3), manageable retroprosthetic membrane (N = 3), intraocular pressure elevation responded to antiglaucoma drugs (N = 2), and Pseudomonas keratitis with severe corneal melting requiring device removal (N = 1). All of our patients failed to have a comfortably well-fitting contact lens after surgery. Conclusions: Boston type 1 keratoprosthesis could be considered as a reasonable option in the management of advanced GDLD. However, patients remain at risk for sight-threatening postoperative complications as long as the keratoprosthesis is retained. The use of Boston keratoprosthesis implantation needed to be individualized on a case-by-case basis.